PERANCANGAN PROGRAM APLIKASI PENYEDIA INFORMASI BUKU BERBASIS WEB DARI BERBAGAI PERPUSTAKAAN - Deddy Supriadi; Derry Apriliandi (Universitas Bina Sarana Informatika Kota Sukabumi, 2015)
Based on the increase of libraries numbers both in the town and village also the amount of books owned by the libraries, the writer tried to give a solution in solving the difficulty to ease the readers in finding the books by using this application system. Based on the research method used in form of requirement analysis that is according to the users’ needs and doing both direct interview and observation around the student neighborhood, the writer concludes that there is a lot of difficulty for students / people in discovering the book they need. Actually, the management of books in all libraries will give a lot of advantageous for them who looking for the books. Thus, it will make them easier and faster to know the location where the particular books they need. Based on the explanation above, the writer made a website to convey facility in order to ease and to accelerate the searching process of the books. This also can intrigue people’s interest in reading. Afterwards, using this algorithm searching system may ease people’s access in getting the books they want just by typing key words for the books they ask.